Penerapan Balanced Scorecard untuk Menilai Kinerja PT XL Axiata Tbk dalam Mencapai Strateginya - Kartika Dewi; Anton Karta Surya (Bina Nusantara University, 2015)
This research is conducted to evaluate performance of PT XL Axiata Tbk using Balanced Score Card. The writer made design and implemented BSC in PT XL Axiata Tbk to convince its vision, mision and strategies are alligned. The method of this research is qualitative descriptive. Primary data were teken through questioners and interviewed with employees and customers.Secondary data were taken from annual report published at company website.The result of this research for Financial Perspective is PT XL Axiata Tbk needs to improve its financial ratio, The result of this research for Customer Perspective is PT XL Axiata Tbk needs to improve its customer satisfaction, The result of this research for Internal Business Process Perspective is PT XL Axiata Tbk needs to maintenance its good result, The result of this research for Learning and Growth is PT XL Axiata Tbk needs to maintenance good working environment. The final conclusion from this research at PT XL Axiata Tbk proved the company performance works toward its strategy, make a continous improvement and make a stable profit through the years taken as a sample.